(untitled) (Boston, 2007)
This Fourteenth Edition of ANNUAL EDITIONS : MANAGEMENT provides convenient, inexpensive access to current articles selected from the best of the public press. Organizational features include: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; a topical index; and an instructor’s resource guide with testing materials. USING ANNUAL EDITIONS IN THE CLASSROOM is offered as a practical guide for instructors.
Keywords: Management,Quản lý